Tundra vegetation stability versus lake-basin variability on the Yukon Coastal Plain (NW Canada) during the past three centuries. (December 2017) - Wolter, Juliane; Lantuit, Hugues; Herzschuh, Ulrike; Stettner, Samuel; Fritz, Michael
Palaeoclimatic reconstructions of the northern Yukon show cooler conditions before AD 1850 followed by gradual warming, and 20th-century temperature measurements indicate decadal-scale temperature fluctuations. The impact of climate on regional vegetation and lake systems has seldom been observed on this scale, however. With this study, we provide a sub-decadal reconstruction of regional vegetation and lake-basin development for the past 300 years, covering the 'Little Ice Age' and the period of recent warming, in low Arctic tundra. We analysed a short lake sediment core from the Yukon Coastal Plain. The age–depth relationship of the core is based on 210 Pb/ 137 Cs validated by AMS radiocarbon dating. We analysed terrestrial pollen abundances as proxies for regional vegetation development, and we used grain size and biogeochemical analyses (TOC, TN, TOC/TN, δ 13 C) and the analysis of semiaquatic pollen to describe the lake development. Stable abundances of regional pollen taxa between AD 1730 and AD 2012 accompanied by climatic warming indicated that the regional vegetation was not sensitive to climate change. Based on changes in TOC/TN, δ 13 C and pollen of shallow-water taxa, we reconstructed an increase in lake water depth after AD 1910 that likely followed climatic warming. We attributed this development to climate-driven thaw subsidence in the lake basin. The impact of widespread permafrost thaw on regional vegetation needs to be better constrained in order to predict the limits of vegetation stability and drivers of lake changes in the region.